The visibility of the scientific production of the faculty ofadministrative and economic sciences – UTN in horizontalsocial networks - Chuquín Cadena, Andrea Paola; Suárez Chuquín, Karina Estefanía; Portilla Chagna, Jaime Everardo; Cadena Povea, Henry Rafael (SATHIRI, 2024)
Social networks have been rapidly integrated into technological, social, cultural, scientific and research development in Latin America and the world, opening new opportunities to make science visible. The objective of this article was to identify the level of visibility of the scientific production of the Faculty of Administrative and Economic Sciences of the UTN in horizontal social networks and delve into the benefits of their use. In this study, quantitative methodology with a descriptive scope was used, through an observation sheet that made it possible to diagnose the reality of the presenceof the research groups in horizontal social networks and a survey directed at the directors of the groups to understand what they are. the causes of your presence or absence on these platforms; resulting in the absence of research groups in these spaces being more relevant. Considering the results provided by the instruments, this work pays particular attention to the platforms Facebook, Instagram, Twitter (now recognized as X) and focuses on conducting a review of the literature andprevious studies that allow identifying the best strategies to generate greater visibility to scientificproduction so that they can be replicated by the university academic community. Horizontal socialnetworks open fields for scientific dissemination and visibility; it is important to focus the content,applying digital strategies for greater effectiveness and rapprochement with the target audience.
Keywords: Social networks; visibility; dissemination; open science